STRATEGI PENANGANAN PEMBIAYAAN BERMASALAH PADA PRODUK PEMBIAYAAN MURABAHAH DI KOPERASI SIMPAN PINJAM KARYA USAHA MANDIRI BOGOR (KSPPS KUMS BOGOR) CABANG JONGGOL - Nanda Suganda; Rully Trihantana; Hasbi Ash Shiddieqy (SAHID BUSINESS JOURNAL, 2021)
ABSTRACT Non-performing financing is financing where there are irregularities in returns that result in delays in payments so that judicial action is needed in return, there is even a possibility that the cooperative will be harmed. The data for NonPerforming Financing KSPPS KUM Bogor Jonggol Branch where in 2018 it was 4% and in 2019 it was 5%. This percentage cannot be said to be good because the NPF ratio is still at 5% in 2019. For that, a strategy is needed that can be used to reduce or even prevent the non-performing financing. So the author took the title "Strategies for Handling Problematic Financing in Murabahah Financing Products in the Sharia Financing Savings and Loans Cooperative Mandiri Mandiri Bogor Branch Jonggol". The formulation of the problem in this study: What are the causes of the occurrence of non-performing financing and what are the strategies used to deal with non-performing financing. The purpose of this research is to analyze the causes of the occurrence of non-performing financing and how the strategies used in dealing with non-performing financing are. The nature of this research is explanatory (explanatory research) with a qualitative approach. The data analysis technique used in this study is descriptive qualitative analysis using a SWOT analysis approach. The result of this study is that there are factors that cause problematic financing where these factors are internal and external factors. The way the cooperative is doing to solve problem financing is by using two ways of stay strategy and phase out strategy. Stay strategy is a strategy where cooperatives still want to maintain business relationships with customers in the long term context, while phase out strategy is a strategy that is carried out when in principle cooperatives do not want to continue business relationships with customers in the context of a long time. Keywords: Problem Financing, SWOT Analysis, Troubled Financing Handling Strategy